2023
DOI: 10.1186/s12933-023-01763-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic proinflammatory−profibrotic response in aortic stenosis patients with diabetes and its relationship with myocardial remodeling and clinical outcome

Abstract: Background Previous studies have mainly focused more on how diabetes affects the valve than the myocardium in aortic stenosis (AS). In the pressure-overloaded heart, myocardial fibrosis is an important driver of the progression from compensated hypertrophy to heart failure. Using comprehensive noninvasive imaging and plasma proteomics, we investigated whether and how diabetes aggravates the remodeling of the myocardium and its relation with prognosis in AS patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“… 12 Indeed, ECV has been associated with markers of disease severity and all-cause mortality in patients with AS, even after aortic valve replacement. 13 We found a small increase in diffuse fibrosis in the diabetes group with AS which is consistent with a previous study that examined preoperative LV biopsies, although in a much smaller sample size (n=16 with diabetes), 14 as well as in the study by Lee et al 11 In diabetes, the mechanism of cardiac fibrosis is complex but may be related to changes in fibroinflammatory markers (such as transforming growth factor or matrix metalloproteinases) 15 which may lead to the deposition of collagen within the extracellular matrix. This can cause increased myocardial stiffness which could help drive the myocardial hypertrophic response from being adaptive to decompensation 1 and contribute to microvascular dysfunction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 12 Indeed, ECV has been associated with markers of disease severity and all-cause mortality in patients with AS, even after aortic valve replacement. 13 We found a small increase in diffuse fibrosis in the diabetes group with AS which is consistent with a previous study that examined preoperative LV biopsies, although in a much smaller sample size (n=16 with diabetes), 14 as well as in the study by Lee et al 11 In diabetes, the mechanism of cardiac fibrosis is complex but may be related to changes in fibroinflammatory markers (such as transforming growth factor or matrix metalloproteinases) 15 which may lead to the deposition of collagen within the extracellular matrix. This can cause increased myocardial stiffness which could help drive the myocardial hypertrophic response from being adaptive to decompensation 1 and contribute to microvascular dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…With a similar length of follow-up (median 6.3 years) compared with our study, Lee et al showed diabetes is significantly associated with outcomes (HR 1.88). 11 Their events, however, were largely driven by all-cause death which would be somewhat consistent with our secondary outcome findings. Other groups have shown that diabetes increases the risk of non-cardiac deaths.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…49 We also conducted an exploratory sensitivity analysis in patients with T2DM. Lee et al 6 demonstrated that T2DM in patients with AS is associated with increased serum levels of pro-inflammatory cytokines, more advanced ventricular diastolic dysfunction, deregulated myocardial fibrosis, and increased risk of HF and death. We show that peak VO 2 is significantly impaired in diabetic versus non-diabetic patients in both ASpEF and HFpEF.…”
Section: Epicardial Adipose Tissuementioning
confidence: 99%
“…arterial hypertension, type 2 diabetes mellitus [T2DM]) are associated with an increased risk of developing AS 4 and with marked cardiac structural and functional abnormalities (i.e. left ventricular diastolic dysfunction, 5,6 diffuse myocardial fibrosis, 5,6 increased systemic inflammation 6 ) independently of AS severity and left ventricular ejection fraction (LVEF). 7,8 Also, these patients are associated with a worse prognosis in AS, even after AV replacement (AVR).…”
Section: Introductionmentioning
confidence: 99%